IMPLEMENTASI SISTEM PAKAR METODE DEMPSTER-SHAFER UNTUK MENDIAGNOSA PENYAKIT DEMAM TIFOID (Typhus Abdominalis) - Resdi Hadi Prayoga (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
Expert systems (expert systems) is a system that uses human knowledge, where knowledge is putinto a computer, and then used to solve problems that normally require human expertise or skill.In this case, the expert system is used to determine the type of disease stage of typhoid fever, inwhich there are several types of typhoid stage that can be experienced by anyone, because it is inthis case, systems of experts is used to help people who want to know the type of typhoid stage inthe suffering , which in this case there are four types of stages are discussed, namely incremasistage, acme stage, stage deternasi and recofalesent stage. In the application of expert systems isaided by using Depmster-Shafer. Dempster-Shafer is a mathematical theory of evidence based onbelief functions and plausible reasoning (belief functions and plausible thinking), which is used tocombine separate pieces of information (evidence) to calculate the likelihood of an event.